Pastclim 1.2: an R package to easily access and use paleoclimatic reconstructions. Issue 3 (5th January 2023) - Leonardi, Michela; Hallett, Emily Y.; Beyer, Robert; Krapp, Mario; Manica, Andrea
Abstract : The recent development of continuous paleoclimatic reconstructions covering hundreds of thousands of years paved the way for a large number of studies from disciplines ranging from paleoecology to archaeology, conservation to population genetics, macroevolution to anthropology and human evolution to linguistics. Unfortunately, (paleo)climatic data can be challenging to extract and analyze for scholars unfamiliar with such specific file formats. Here we present pastclim, an R package facilitating the access and use of paleoclimatic reconstructions. It currently includes two of such datasets, covering respectively the last 120 000 and 800 000 years, and a vignette provides instructions on how to include additional datasets. The package contains a set of functions to quickly and easily recover the climate for time periods of interest either for the whole world or specific areas, extract data from locations scattered in space and/or time, retrieve time series from individual sites, and manage the ice or land coverage, offering a handy platform to include the climate of the past into existing or new analyses and pipelines.